Implementation of the fiscal rule in Costa Rica - Conejo Fernández, Carlos (2020)
As a consequence of the increasing deterioration of public finances in the last ten years, Costa Rica approved a fiscal rule that links growth of public spending with growth of national production and level of public debt. The rule was implemented in 2020. The objective of this article is to highlight the risk of adverse results if the fiscal rule restricts public expenditure excessively. Regarding the verification of compliance with the fiscal rule, according to the Ministry of Treasury the budget formulated for the respective year should be used as a parameter, while according to the Comptroller General of the Republic what must be used is the budget effectively executed by each of the public entities. A simple linear simulation model is applied here to calculate the possible trends that public spending will follow when using each of the indicated parameters for verification. It is concluded that a very restrictive interpretation of the fiscal rule could generate unwanted results. In addition, it is pointed out that with the health emergency caused by the Coronavirus, the fiscal rule rather restricts the government’s freedom when greater flexibility is needed to manage the fiscal policy.